2021
DOI: 10.1016/j.critrevonc.2021.103433
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for individuals with bone metastases: A systematic review

Abstract: BackgroundExercise has the potential to improve physical function and quality of life in individuals with bone metastases but is often avoided due to safety concerns. This systematic review summarizes the safety, feasibility and efficacy of exercise in controlled trials that include individuals with bone metastases. Methods MEDLINE, Embase, Pubmed, CINAHL, PEDro and CENTRAL databases were searched up to July 16, 2020. ResultsA total of 17 trials were included incorporating aerobic exercise, resistance exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 58 publications
1
44
0
1
Order By: Relevance
“…Nonetheless, every study reporting a significant effect reported relative maintenance or gain of lean mass in the intervention group compared to control. This trend favoring the intervention groups suggests a possible effect of exercise both with and without a nutritional component and builds upon congruent findings in existing reviews [ 44 , 57 , 58 ]. The combination of resistance training and increased protein intake has been associated with lean mass preservation or increased muscle protein synthesis among patients with cancer [ 88 , 89 , 90 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nonetheless, every study reporting a significant effect reported relative maintenance or gain of lean mass in the intervention group compared to control. This trend favoring the intervention groups suggests a possible effect of exercise both with and without a nutritional component and builds upon congruent findings in existing reviews [ 44 , 57 , 58 ]. The combination of resistance training and increased protein intake has been associated with lean mass preservation or increased muscle protein synthesis among patients with cancer [ 88 , 89 , 90 ].…”
Section: Discussionsupporting
confidence: 85%
“…Exercise has emerged as an effective therapeutic adjunct to conventional cancer therapies and has been shown to improve the quality of life and physical function of patients with cancer [ 42 ]. However, patients with metastatic or advanced cancer remain largely understudied compared to patients at other stages [ 43 ], although emerging evidence suggests exercise to be safe for this population [ 44 , 45 ]. Despite the likely benefits of exercise in this population, changes to body composition also depend on nutritional status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study reported zero serious adverse events (≥3 CTCAE grading criteria) and twelve study-related grade one events (increased muscular or joint soreness and acute fatigue levels). A recent systematic review in individuals with bone metastases supports the use of unsupervised exercise as long as there is a supervised component, including face-to-face exercise instruction [ 66 ]. The novel use of distance-based supervision may provide another safe method of instruction by qualified practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Ein ähnliches Problem zeigt sich auch bei vielen der benannten Kontextfaktoren, bei denen die befragten HCP keine Einstimmigkeit zeigten. Beispielsweise liegen erst seit Kurzem systematische Aufarbeitungen der Literatur zum Training mit Patienten mit Knochenmetastasen inklusive praktischer Implikationen vor 14 15 . Trotz der im Grunde äußerst positiven Einstellung gegenüber Bewegung konnte beobachtet werden, dass es noch immer HCP gibt, welche weiterhin an der längst überholten Idee festhalten, dass Patienten sich schonen sollten.…”
Section: Diskussionunclassified